Investigation of the soil properties that affect Olsen P critical values in different soil types and impact on P fertiliser recommendations. (26th January 2021) - Tandy, Susan; Hawkins, Jane M. B.; Dunham, Sarah J.; Hernandez‐Allica, Javier; Granger, Steve J.; Yuan, Huimin; McGrath, Steve P.; Blackwell, Martin S. A.
Abstract: Optimization of phosphorus (P) fertiliser use is desired to ensure more sustainable use of fertiliser, economic food production and reduction of eutrophication of water bodies. Presently, the Olsen P values on which fertiliser recommendations are based to achieve optimum yield are frequently the same for all soils. The aim of this study was to identify the properties of different soils that affect their critical Olsen P values in order to develop better, soil‐specific P fertiliser recommendations. A pot experiment using 10 soils with low available P with different P additions was carried out to investigate the impact of wide‐ranging soil properties on the relationship between P addition, resultant Olsen P values and yield response of ryegrass to Olsen P values. The relationship between added P and Olsen P varied greatly between the individual soils. These relationships were affected by pH, manganese oxide, crystalline aluminium oxide and amorphous iron oxide contents of the soil. Different soils had widely varying critical Olsen P values for ryegrass. However, these could not be related to the measured soil properties. Fertiliser recommendations and critical values for optimum yield of ryegrass based on the Olsen P test should be soil specific. The complexity and lack of clarity over which combination of soil properties governs critical Olsen P values calls for further investigation with more soil types and additional soil property measurements to elucidate the different factors controlling critical Olsen P values in different soils. Highlights: Soil‐specific P fertiliser recommendations are needed for sustainable fertiliser use We investigated soil properties affecting critical Olsen P values and added P fertiliser availability Fertiliser P availability was affected by pH and metal (hydr)oxide contents of the soil Critical Olsen P values varied with soil, but measured soil properties could not explain this variation